Using experience characteristics and coping strategies to understand visitor support for a national park managed access system: case study of arches National Park - Iree Wheeler; Wayne Freimund; Ryan Knowles (Journal of Outdoor Recreation and Tourism, 2025)

Component identification of solid biomass fuels using reflected light microscopy: Interlaboratory study 2 - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Menandro N. Acda; Tushar Adsul; Neža Malenšek Andolšek; Lorenzo Animali; Omid H. Ardakani; Telma Ataide; Demberelsuren Batbold; Mohd Younus Bhat; et al. (International Journal of Coal Geology, 2025)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Genetic subdivision and candidate genes under selection in North American grey wolves - Rena M. Schweizer; Bridgett M. vonHoldt; Ryan Harrigan; James C. Knowles; Marco Musiani; David Coltman; John Novembre; Robert K. Wayne (Molecular Ecology, 2016)
Previous genetic studies of the highly mobile grey wolf ( Canis lupus ) found population structure that coincides with habitat and phenotype differences. We hypothesized that these ecologically distinct populations (ecotypes) should exhibit signatures of selection in genes related to morphology, coat colour and metabolism. To test these predictions, we quantified population structure related to habitat using a genotyping array to assess variation in 42 036 single‐nucleotide polymorphisms (SNPs) in 111 North American grey wolves. Using these SNP data and individual‐level measurements of 12 environmental variables, we identified six ecotypes: West Forest, Boreal Forest, Arctic, High Arctic, British Columbia and Atlantic Forest. Next, we explored signals of selection across these wolf ecotypes through the use of three complementary methods to detect selection: F ST /haplotype homozygosity bivariate percentilae, bayescan , and environmentally correlated directional selection with bayenv . Across all methods, we found consistent signals of selection on genes related to morphology, coat coloration, metabolism, as predicted, as well as vision and hearing. In several high‐ranking candidate genes, including LEPR , TYR and SLC14A2 , we found variation in allele frequencies that follow environmental changes in temperature and precipitation, a result that is consistent with local adaptation rather than genetic drift. Our findings show that local adaptation can occur despite gene flow in a highly mobile species and can be detected through a moderately dense genomic scan. These patterns of local adaptation revealed by SNP genotyping likely reflect high fidelity to natal habitats of dispersing wolves, strong ecological divergence among habitats, and moderate levels of linkage in the wolf genome.

Implications for Future Survival of Delta Smelt from Four Climate Change Scenarios for the Sacramento–San Joaquin Delta, California - Larry R. Brown; William A. Bennett; R. Wayne Wagner; Tara Morgan-King; Noah Knowles; Frederick Feyrer; David H. Schoellhamer; Mark T. Stacey; Michael Dettinger (Estuaries and Coasts, 2013)

Statistical Phylogeography - L. Lacey Knowles; Wayne P. Maddison (Molecular Ecology, 2002)

Statistical phylogeography - L. Lacey Knowles; Wayne P. Maddison (Molecular Ecology, 2002)